Transumbilical laparoendoscopic single‐site surgery versus conventional laparoscopy for the resection of retroperitoneal paragangliomas. (26th June 2015) - Xu, Weifeng; Li, Hanzhong; Ji, Zhigang; Yan, Weigang; Zhang, Yushi; Zhang, Xuebin; Li, Qian
<x xml:space="preserve">Abstract</x> Objectives To compare transumbilical laparoendoscopic single‐site surgery with conventional laparoscopy for the resection of retroperitoneal paragangliomas. Methods In the present case–control study, we compared 11 transumbilical laparoendoscopic single‐site surgery procedures with 22 conventional laparoscopy procedures carried out to treat retroperitoneal paragangliomas between June 2004 and October 2013 at Peking Union Medical Hospital, Beijing, China. Operative time, estimated intraoperative blood loss, blood transfusions, intraoperative hypertension, intraoperative hypotension, highest intraoperative systolic blood pressure, lowest intraoperative systolic blood pressure, postoperative fatigue time, postoperative systematic inflammation reaction syndrome, 24‐h postoperative visual analog scale scores, postoperative hospital stay duration, and postoperative complications were recorded and analyzed. Results There were no significant differences in patient characteristics. All surgical procedures were successfully completed in both groups. Minor complications occurred in one case in the laparoendoscopic single‐site surgery group and in two cases in the conventional laparoscopy group. In the laparoendoscopic single‐site surgery group, the operative time was longer than that in the conventional laparoscopy group (P = 0.001). There were no significant differences in terms of intraoperative hypertension, intraoperative hypotension, highest intraoperative systolic blood pressure, lowest intraoperative systolic blood pressure, estimated blood loss, postoperative fatigue time, postoperative hospital stay or systematic inflammation reaction syndrome between the two groups. The 24‐h postoperative visual analog scale score was lower in the laparoendoscopic single‐site surgery group (P = 0.002). No recurrence or metastases were observed over the duration of the postoperative follow up. Conclusions In properly selected patients, transumbilical laparoendoscopic single‐site surgery is a feasible, safe and effective procedure for the surgical treatment of retroperitoneal paragangliomas.